Appraisal of Microbial Evolution to Commensalism and Pathogenicity in Humans - Ghosh, Asit Ranjan (Libertas Academica, 2013)
The human body is host to a number of microbes occurring in various forms of host-microbe associations, such as commensals, mutualists, pathogens and opportunistic symbionts. While this association with microbes in certain cases is beneficial to the host, in many other cases it seems to offer no evident benefit or motive. The emergence and re-emergence of newer varieties of infectious diseases with causative agents being strains that were once living in the human system makes it necessary to study the environment and the dynamics under which this host microbe relationship thrives. The present discussion examines this interaction while tracing the origins of this association, and attempts to hypothesize a possible framework of selective pressures that could have lead microbes to inhabit mammalian host systems.